Visual electrophy siological tests in obstructive sleep apnoea - Seok, Hui Ng; Tai, Evelyn Li Min; Abdullah, Baharudin; Mohd Noor, Raja Azmi; Wan Hitam, Wan-Hazabbah (Press of International Journal of Ophthalmology, 2017)
AIM:To compare the pattern electroretinogram (PERG) and pattern visual evoked potential ( PVEP ) between obstructive sleep apnoea (OSA) patients and controls. METHODS: This was a prospective cross - sectional study involving 40 OSA patients and 31 control subjects in Hospital Universiti Sains Malaysia. Patients with a confirmed diagnosis of OSA who had no ocular pathology were randomly selected to participate in the study. The apnoea-hypopnoea index (AHI) was obtained from their records and used for stratification of OSA severity. Electrophysiological tests ( PVEP and PERG ) were performed on each patient by a trained technician in the electrophysiology laboratory of the Department of Ophthalmology, USM. The results obtained were recorded as median values. Data analysis was done using IBM Statistics Version 21. 0. RESULTS: Among OSA patients, we observed a significant reduction of the PERG amplitude P50 ( P < 0.001) and the PVEP amplitude P100 (P<0. 001) compared to the control group. OSA patients also had a significant increase in PVEP time to peak P100 (P = 0. 003) and time to peak N75 (P = 0. 004). However, no significant differences were detected in PERG time to peak between OSA patients and controls. There were likewise no significant differences in PVEP or PERG between OSA patients with different disease severity. CONCLUSION: OSA patients have significant abnormalities in PVEP amplitude and time to peak, as well as PERG amplitude. This may reflect subclinical optic nerve dysfunction in OSA. Further research is needed to determine the association between the severity of OSA and the degree of optic nerve dysfunction.